Selected Aspects of Quality of Life in Information Society: Regional Study Focused on Hearing-impaired Citizens - Jirava, Pavel; Kašparová, Miloslava; Křupka, Jiří; Mandys, Jan; Chlumecký, Václav (International Business Information Management Association-IBIMA, 2018)
Citizens with disability are indisputably an integral part of the society with specific needs. For improvement of public services for them, we need to examine their daily needs. This paper focuses on selected aspects of quality of life for deaf and hard-of-hearing people on the regional level. Emphasis is put on the issue of education and access to internet. Citizens with hearing problems in the region in the Czech Republic are the target group. Selected methods are used to analyses of the data obtained from survey. The results are discussed and compared with expectations. It turns out that in relevant areas (as in educational attainment, use the internet, unemployment) the respondents are in a worse position than the normal hearing population. The results of this study can be used as a basis for decisions by public authorities in the areas of social, educational and information policy, at the regional or state level.
Vybrané aspekty kvality života v informační společnosti - regionální studie zaměřená na sluchově postižené
Keywords: Quality of Life; Information Society; Regional Study; Hearing-impaired Citizens; Kvalita života; informační společnost; sluchově postižení; region